Security of Iris Recognition and Voice Recognition Techniques - Raoof, Ayad R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Recently, biometric technologies are used widely due to their improved security that decreases cases of deception and theft. The biometric technologies use physical features and characters in the identification of individuals. The most common biometric technologies are: Iris, voice, fingerprint, handwriting and hand print. In this paper, two biometric recognition technologies are analyzed and compared, which are the iris and sound recognition techniques. The iris recognition technique recognizes persons by analyzing the main patterns in the iris structure, while the sound recognition technique identifies individuals depending on their unique voice characteristics or as called voice print. The comparison results show that the resultant average accuracies of the iris technique and voice technique are 99.83% and 98%, respectively. Thus, the iris recognition technique provides higher accuracy and security than the voice recognition technique